Application and Evaluation of Regional Control Technology of Limestone Water Hazard: A Case Study of the Gubei Coal Mine, North China. (9th April 2021) - Zhu, Jingzhong; Liu, Yu; Liu, Qimeng; Yang, Sen; Fan, Jiajun; Cui, Yu; Li, Ling
Abstract : The coal-forming period is mainly Permian and Carboniferous in the North China coalfield, which is one of the main coal accumulating areas in China. It is characterized by high coal rank, abundant reserves, and varieties. However, water outburst accidents originating from karst aquifers under the coal seam floor have become a terrible disaster in accompany with the deep coal exploited progressively. Water inrush events of the deep limestone have often occurred during excavation in mines. To decrease the risk of high confined water from the coal seam floor and ensure the mining under the safe water pressure of limestone aquifers, the comprehensive exploration and regional treatment are all implemented, such as drainage depressurization, curtain grouting, and grouting transformation of aquifers. Through the comprehensive treatment of the ground and underground, the water channel will be effectively filled with slurry to prevent limestone water bursting into the roadway, and the value of water-inrush coefficient is decreased below the critical value. In the study, utilizing COMSOL Multiphysics based on the finite element method to verify and determine the real layout of grouting parameters, the result shows the design plans satisfy the engineering requirements. 13321 working face located in South No.1 mining area has analyzed the effect of water hazard prevention and control. On the basis of the analysis of geophysical prospecting and validation boreholes, it is concluded that the fracture is filled with grouting slurry to block water-conducting channel effectively. In turn, the rational design parameters of grouting are confirmed as well. Finally, the water-inrush coefficient of Taiyuan formation limestone and Ordovician limestone water is calculated, respectively. The result shows that water-inrush coefficient is less than the critical value after treatment, the safety of excavating coal seam can be further assured.